Kajian Pemilihan Jenis Kolam Olak Dari Segi Fisik Bendung Pada Bendung Di Dusun Darok - Saputra, Darma Tinto ; Khaerudin , Dian Noorvy ; Sulistyani , Kiki Frida (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
The occurrence of a hydraulic jump will cause scouring and damage to the energy damper in the form of an olak pond in the weir so that it can reduce the risk of the weir. Then it needs to be repaired olak pond in the weir by using a new olak pond. . In this case the researcher will conduct a Study of Pool Type Selection in terms of the Physical Weir of the Weir in the Dusun Darok. The objective to be achieved in this research is to study what kind of olak ponds are suitable in the weir in Dusun Darokt. From the results of research and research on the condition of the weir in the field, the weir structure was built with stone pairs, cross section of the weir in the form of a trapezoid with a slope of m = 0.5, the height of the dam lighthouse = +171.4 and the height of the roof floor of the room = +167, in accordance with the height between the olak floor to the lighthouse (D), which is: 171.4 - 167 = 4.4 m. The results of the analysis and discussion, olak pond types USBR I, USBR II, USBR III and USBR IV, do not meet the requirements and cannot be applied and the type of olak pond pool meets the requirements and can be applied to dams in Dusun Darok.